Development and Biomass Composition of Ephestia kuehniella (Lepidoptera: Pyralidae), Tenebrio molitor (Coleoptera: Tenebrionidae), and Hermetia illucens (Diptera: Stratiomyidae) Reared on Different Byproducts of the Agri-Food Industry. Issue 4 (18th August 2020) - Riudavets, Jordi; Castañé, Cristina; Agustí, Nuria; del Arco, Lidia; Diaz, Isabel; Castellari, Massimo
Abstract: The aim of this study was to evaluate five agro-industrial byproducts (apricots, brewer's spent grains, brewer's spent yeast, feed mill byproducts including broken cereal grains, and hatchery waste including eggshell debris, fluff, infertile eggs, dead embryos, and egg fluids) or mixtures thereof as food diets of Ephestia kuehniella (Zeller), Tenebrio molitor (L.), and Hermetia illucens (L.) . Eleven out of 26 tested combinations allowed the first instar larvae to reach the adult stage. Results showed that bioconversion parameters and biomass composition can vary depending on the diet composition, especially in the case of E. kuehniella and H. illucens, whose nutritional requirements seem more complex than those of T. molitor . Tenebrio molitor was able to develop in almost all byproducts. However, only when T. molitor was fed with suitable mixtures of byproducts the development parameters were similar to those obtained with the standard diet. The best results in terms of bioconversion parameters were obtained by feeding H. illucens with a diet including dried brewer's spent grain, feed mill byproducts and brewer's spent yeast. The larvae of these three species can be considered interesting from a nutritional point of view, because of their high protein and fat content. However, the fatty acids profile of H. illucens larvae, with high proportions of saturated fatty acids, seems less healthy for human consumption compared with those of E. kuehniella and T. molitor .